AHP COMPARATIVE JUDGEMENT ON MOBILE COMMERCE COMPUTER SHOP APPLICATION IN SEMARANG CITY USING GOOGLE MAPS API BASED ANDROID - Daru, April Firman; Khoirudin, Khoirudin; Widodo, Muhammad Faizal Agung (Universitas Semarang, 2017)
In terms of activities in computer stores, many potential customers who come, then go home without making a transaction. This happens because consumers who come to the store want to know the price information, brand stock, and promotion first and then compare it with other stores. The decision recommendations generated by AHP are approaching expectations as they are examined from different perspectives and this method is very applicable to anyone decision makers because input is not only based on logic in general, but also intuition. The prototyping model implements rapid development and testing of the working model of new applications through repeated interaction processes. The object priority used based on AHP Comparative Judgment inference system calculation is (1) stock; (2) price; (3) distance (location). the process of comparison between criteria has been performed in a consistent manner consistent with the random consistency index of the normative analytical hierarchy process comparative judgment matrix. So that the output list that is displayed to the user can be used as the best reference product selection. Implementation of computer information system store application in Semarang City with AHP (Analyitical Hierarchy Processs) Comparative Judgment method can be accessed by Android users to recommend products to be purchased based on the criteria of availability of goods, price and distance practically anytime and anywhere.